Z badań nad umiejętnościami intelektualnymi i procesami poznawczymi osób w spektrum autyzmu – perspektywa rozwojowa i edukacyjna - Winczura, Barbara (Studia Edukacyjne, 2024)
Autism is a specific neurodevelopmental disorder that mainly involves abnormalities in social interaction, difficulties with communication and social communication, and limited, repetitive patterns of behavior, interests, or activities. These abnormalities can be described on a continuum, specifying different degrees of their severity. The development of intellectual abilities of people with autism spectrum disorders is disharmonious and highly differentiated both in the entire population and in individual cases. There is no clear profile of intellectual abilities typical of autism. Moreover, the accurate measurement of intellectual abilities and their adequate assessment of development in this group of people is quite challenging. In addition to many deficits in specific areas, some people exhibit exceptional skills in other areas. The results of many studies indicate profile differences in the cognitive abilities of people on the autism spectrum. The article offers the characteristics of cognitive difficulties and the presentation of research on intellectual abilities in this group of disorders. Recognizing the specific cognitive functions and intellectual capabilities of people on the autism spectrum is a key element in the diagnostic process which enables prediction of educational opportunities and determines the selection of appropriate methods and therapeutic agents.